Study on rock-breaking efficiency evaluation of TBM disc cutters based on Rostami prediction equations - Zhou, Guanghong; Wang, Xuchun; Wang, Ding; Luo, Minhe; Hao, Zhanpeng; Wu, Wenrui (Frontiers in Earth Science, 2023)
As the main cutting tool of Tunnel Boring Machine (TBM) for rock-breaking, the rock-breaking efficiency of TBM disc cutters directly affects the TBM’s boring speed, which in turn affects the overall progress of the tunnelling project. Therefore, a simple and accurate evaluation method of the rock-breaking efficiency of TBM disc cutters is an essential prerequisite to improve the rock-breaking performance of TBM. In this paper, the classical force prediction equations of disc cutters were summarized and the applicability of each equation for the constant cross-section disc cutters was analyzed. The calculation equation of the specific energy per ring of TBM rock-breaking was derived based on the Rostami prediction equations and the specific energy theory for disc cutter rock-breaking. The specific energy per ring equation was verified through a practical engineering case. The results show that the maximum relative error of the effective thrust force and the effective torque of the cutter head based on the Rostami force prediction equations is 9.8%. The relative error of the specific energy per ring is 8.0%, which indicates that the prediction of the specific energy per ring equation can accurately reflect the rock-breaking efficiency of disc cutters. The derived equation of the specific energy per ring can not only simplify the rock-breaking efficiency evaluation of TBM disc cutters, but also serve as a valuable reference for practical engineering projects.